The -514C/T Polymorphism of Hepatic Lipase Gene Among Iranian Patients with Coronary Heart Disease - M Darabi Amin; E Farrokhi; M Hashemzadeh Chaleshtory; M Rohbani Nobar; M Noori; K Ghatreh Samani (Tehran University of Medical Sciences, 2012)
Background: The T allele of the hepatic lipase (HL) C-514T polymorphism was previously found to be associated with lower plasma HL activity. Here, we examined the association between this polymorphism and plasma HDL-cholesterol concentrations in patients with coronary arteries stenosis.Methods: We studied 342 subjects undergoing coronary angiography in two groups of non CAD (n=146) and CAD (n=196). -514C→T polymorphism was determined using polymerase chain reaction and restriction fragment length polymorphism (PCR-RFLP).Results: After adjustment for age, smoking and body mass index, HDL-cholesterol concentrations were significantly higher in men with the C/T&T/T genotype than those with the C/C genotype(mean 38.6 and 34.7 respectively P=0.01). The frequency of T allele in non CAD was 0.136 and 0.226 in female and male respectively and 0.170 and 0.223 for female and male in CAD subjects. There was no difference in T allele frequency in CAD and none CAD groups in male and female (P=0.466 and 0.722 respectively).Conclusion: -514C→T of LIPC gene have a positive effect on HDL-C concentration especially in male gender. However, no difference was determined in frequency of T allele between CAD and normal arteries subjects.